Improving Antioxidative and Antiproliferative Properties Through the Release of Bioactive Compounds From Eucommia ulmoides Oliver Bark by Steam Explosion - Kong, Feng; Zeng, Qinghua; Li, Yue; Ding, Yishuai; Xue, Di; Guo, Xingfeng (Frontiers in Nutrition, 2022)
Eucommia ulmoides Oliver bark is a potential medicinal plant-based feedstock for bioactive products and possesses the effective functions of antioxidant and antitumor. Network pharmacology was employed to reveal the oxidative and free radical damage and cancer-related potential compounds of Eucommia ulmoides Oliver in this study. The result showed that quercetin might be the key compound to resist these two types of diseases. Then, the effect of steam explosion on the release of bioactive compounds and the antioxidative and antiproliferative properties of the extract from Eucommia ulmoides Oliver bark were investigated. Results showed that steam explosion at 0.7 MPa for 30 min significantly enhanced the total phenolic, total flavonoids, and quercetin content of Eucommia ulmoides Oliver bark. Reducing power and 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) radical scavenging activity of the steam-exploded extracting solution were 1.72 and 2.76 times of native. The antiproliferative activity to CT26 and HepG2 of the extract from steam-exploded Eucommia ulmoides Oliver bark (SEU) was higher than those of native-exploded Eucommia ulmoides Oliver bark (NEU). All these results suggested that steam explosion could be applied to release the bioactive compounds, thus enhanced the antioxidative and antiproliferative activities of medicinal and edible plant-based sources.